2016
DOI: 10.1136/bcr-2016-217195
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cryptococcosis in an immunocompetent child

Abstract: Cryptococcus is a ubiquitous fungus and is known for causing meningitis and cutaneous infections in immunocompromised individuals. Disseminated cryptococcal infection is very rare and almost always found to occur in immunocompromised individuals especially in persons infected with HIV. This is particularly attributed to its capsulated spores. But there are few reported cases in which it has been found to cause disseminated infections even in immunocompetent individuals. We report a similar case of disseminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Direct transmission between people or animals appears to be rare, but a previous study showed that symptoms of Cryptococcus infection can occur after birth from an asymptomatic mother, possibly indicating that placental infection can lead to a potentially serious condition (14). PC occurs commonly in ICH individuals, such as in AIDS patients, but can occur in NICH individuals as well (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Direct transmission between people or animals appears to be rare, but a previous study showed that symptoms of Cryptococcus infection can occur after birth from an asymptomatic mother, possibly indicating that placental infection can lead to a potentially serious condition (14). PC occurs commonly in ICH individuals, such as in AIDS patients, but can occur in NICH individuals as well (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%